2020
DOI: 10.1101/2020.09.30.20204875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HLA allele-specific expression loss in tumors can shorten survival and hinder immunotherapy

Abstract: Efficient presentation of aberrant peptide fragments by the human leukocyte antigen class I (HLA-I) genes is necessary for immune detection and killing of cancer cells. Patient HLA-I genotypes are known to impact the efficacy of cancer immunotherapy, and the somatic loss of HLA-I heterozygosity has been established as a factor in immune evasion. While global deregulated expression of HLA-I has been reported in different tumor types, the role of HLA-I allele-specific expression loss - that is, the preferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…By accounting for these escape mechanisms, and combining them into a composite neoantigen score, we captured a fuller representation of tumor antigen presentation to the immune system compared to simpler models such as TMB, increasing the predictive strength of this biomarker. This approach will likely yield exciting results when applied to non–small cell lung carcinoma and squamous cell carcinoma of the head and neck patient cohorts, as HLA LOH is a prevalent escape mechanism in these, and other tumor types ( 49 ). Indeed, work by Filip and colleagues ( 49 ) which leverages data from >3,500 tumors found allele-specific expression loss at frequencies above 45% in head and neck, lung adenocarcinoma, pancreatic, and prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By accounting for these escape mechanisms, and combining them into a composite neoantigen score, we captured a fuller representation of tumor antigen presentation to the immune system compared to simpler models such as TMB, increasing the predictive strength of this biomarker. This approach will likely yield exciting results when applied to non–small cell lung carcinoma and squamous cell carcinoma of the head and neck patient cohorts, as HLA LOH is a prevalent escape mechanism in these, and other tumor types ( 49 ). Indeed, work by Filip and colleagues ( 49 ) which leverages data from >3,500 tumors found allele-specific expression loss at frequencies above 45% in head and neck, lung adenocarcinoma, pancreatic, and prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This approach will likely yield exciting results when applied to non–small cell lung carcinoma and squamous cell carcinoma of the head and neck patient cohorts, as HLA LOH is a prevalent escape mechanism in these, and other tumor types ( 49 ). Indeed, work by Filip and colleagues ( 49 ) which leverages data from >3,500 tumors found allele-specific expression loss at frequencies above 45% in head and neck, lung adenocarcinoma, pancreatic, and prostate cancers. This, combined with the well-documented prevalence of somatic mutations in class I HLA genes suggests a broad pervasiveness of damaging APM events captured by NEOPS.…”
Section: Discussionmentioning
confidence: 99%
“…ArcasHLA, a python-based pipeline was initially developed for HLA genotyping from RNA-seq reads using kallisto, however, the authors later added the feature for allele-specific expression quantification currently allowing both highly accurate HLA typing and expression analysis ( 66 ). By using this novel pipeline, the authors analyzed the clinical significance of HLA class I LOH in multiple tumor types using public RNA-seq data ( 75 ).…”
Section: Methods In Hla Expression Quantificationmentioning
confidence: 99%
“…Regulation of HLA expression also extends to the level of individual alleles ( 6 ). Temporal patterns in allele-specific expression (ASE) of certain HLA-DQB1 alleles can discriminate their relative association with type 1 diabetes ( 7 ) and increased ASE imbalance of MHC class I genes was observed in colorectal ( 8 ) and other cancers ( 9 ). Single-cell sequencing allows for fine resolution of ASE and such studies have demonstrated much of the transcriptome is mono-allelically expressed at a given point in time ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%